The SegBus platform – architecture and communication mechanisms - Seceleanu, Tiberiu (Journal of systems architecture, 2007)
In this study, we introduce the SegBus architecture, a synchronous segmented bus platform for systems on chip. We present the envisioned structure in detail, and also address aspects of communication on the platform. The motivation behind SegBus is the search for performance improvements, in several directions, such as global throughput, power consumption, modularity, adaptability. By means of an example, we illustrate the capabilities of the described architecture. The implementation strategy targets FPGA technology, and allows for the utilization of multiple clock domains. The platform emerges as a highly design-time configurable system, adaptable to various design constraints.